2021
DOI: 10.5603/cj.a2021.0088
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of atrial fibrillation in COVID-19 patients

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…However, maintaining the DOAC during admission was not associated with increased mortality. In this sense, some authors have also observed these findings of benefit from the use of DOACs in patients with COVID-19 infection who required hospital admission 22 .…”
Section: Discussionmentioning
confidence: 84%
“…However, maintaining the DOAC during admission was not associated with increased mortality. In this sense, some authors have also observed these findings of benefit from the use of DOACs in patients with COVID-19 infection who required hospital admission 22 .…”
Section: Discussionmentioning
confidence: 84%
“…A recent meta-analysis showed that the prevalence of new-onset atrial fibrillation in hospitalized patients with COVID-19 was 7.4% [ 29 ]. LMWH can be suggested as the preferred anticoagulation regimen for hospitalized patients with COVID-19 and new-onset atrial fibrillation with a high CHA₂DS₂-VASc score, especially those with critical disease, mainly due to the abovementioned fewer interactions, whereas DOACs would be preferred for long-term anticoagulation afterwards [ 30 ]. A recent Good Practice Guidance Statement by the International Society on Thrombosis and Haemostasis (ISTH) also recommends LMWH as the anticoagulant of choice for hospitalized patients with COVID-19 [ 31 ].…”
Section: Results—key Questions and Practical Recommendationsmentioning
confidence: 99%
“…Sin embargo, el mantener el ACOD durante el ingreso no se asoció con un aumento de la mortalidad. En este sentido, algunos autores también han observado estos hallazgos de beneficio del empleo de ACOD en pacientes con infección por COVID-19 que requirieron ingreso hospitalario 22 .…”
Section: Discussionunclassified